Unlocking the potential of underground hydrogen storage for clean energy solutions - Dodangoda, Chatura; Ranjith, P. G.; Haque, A. (Geomechanics and geophysics for geo-energy and geo-resources., 2024)
This review paper provides a critical examination of underground hydrogen storage (UHS) as a viable solution for large-scale energy storage, surpassing 10 GWh capacities, and contrasts it with aboveground methods. It exploes into the challenges posed by hydrogen injection, such as the potential for hydrogen loss and alterations in the petrophysical and petrographic characteristics of rock structures, which could compromise the efficiency of UHS systems. Central to our analysis is a detailed overview of hydrogen solubility across various solvents, an extensive database of potential mineralogical reactions within underground storage environments, and their implications for hydrogen retention. We particularly focus on the effects of these reactions on the porosity of reservoir and cap rocks, the role of diffusion in hydrogen loss, and the consequences of multiphase flow induced by hydrogen injection. Our findings highlight the critical mineralogical reactions—specifically, goethite reduction and calcite dissolution—and their pronounced impact on increasing cap rock porosity. We underscore a notable discovery: hydrogen's solubility in non-aqueous phases is significantly higher than in aqueous phases, nearly an order of magnitude greater. The paper not only presents quantitative insights into the mechanisms of hydrogen loss but also pinpoints areas in need of further research to deepen our understanding of UHS dynamics. By identifying these research gaps, we aim to guide future studies towards enhancing the operational efficiency and safety of UHS facilities, thereby supporting the transition towards sustainable energy systems. This work is pivotal for industry stakeholders seeking to optimize UHS practices, ensuring both the effective utilization of hydrogen as a clean energy carrier and the advancement of global sustainable energy goals. Article highlights A chemical database of possible reactions with hydrogen was developed, and diffusion and solubility were quantified. Calcite can trigger hydrogen loss by ~ 74%, and carbonates and goethite can increase the porosity. Gravity segregation can increase hydrogen contact with the cap rock and may lead to an increased diffusion loss.